The Impact of Broadband Access on Social and Economic Integration: Results from the RefugeeMobile Pilot. (26th August 2019) - Evans, William N; Perry, Brendan; Factor, Rachel
Abstract: The Internet is a ubiquitous feature of everyday life and an important research question is whether improving broadband access for at-risk groups such as refugees enhances social and economic outcomes. The article reports the results of the RefugeeMobile pilot where a sample of refugees to the United States were randomly assigned a smartphone ( n = 82) with eight months of free service and pre-loaded apps designed to help them adjust to life in the United States, or not ( n = 74). At a one-year follow-up, results indicate that assignment to treatment generates statistically significant increases in smartphone ownership and Internet access, and some measures of social integration. Results for employment and earnings were positive but statistically insignificant. Treatment-group members had fewer interactions with their case worker, a smaller fraction of in-office visits and hence a larger fraction of interactions by phone than control-group members, suggesting the pilot may have increased programme efficiency.